The ghosts of Cannae : Hannibal and the darkest hour of the Roman republic - O'Connell, Robert L. (Random House, 2010)
Robert L. O'Connell, one of the most admired names in military history, tells the whole story of Cannae for the first time, giving a stirring account of this apocalyptic battle of the Second Punic War, and its causes and consequences.